TYPOLOGY OF FEATURES CHARACTERISTIC OF THE CHILD'S PSYCHE IN THE WORK OF MARK TWAIN (ON THE EXAMPLE OF THE WORK OF TOM SAWYER AND GEKBERRY FINN) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The creative legacy of Mark Twain amazes with the richness of its genre repertoire. From his mouth and from his pen, a wide variety of works were born - from aphorism and witticism in one or two phrases to a thousand—page autobiography, from brief newspaper information and reportage to large books of travel notes, from hilariously funny stories to serious philosophical dialogue, from anecdote and fiction to novels recognized as a national epic - factography, journalism, fiction. He also wrote poetry and plays, but above all he became a great master of fiction.